Industrial Policy for Growth and Diversification : A Conceptual Framework - Cherif, Reda (Departmental Papers; Departmental Paper, 2022)
As countries strive for a strong recovery and to recoup the losses incurred during the COVID-19 pandemic, they need to map out a new path for development and high and sustained growth. Promoting diversification, developing new industrial capabilities, and designing the policies needed to achieve this goal should be a priority. A successful diversification strategy should tackle both broad policy failures, such as an unfavorable business environment and investment climate and sector-specific market failures. This departmental paper presents a conceptual framework to analyze industrial policy, defined as targeted sectoral interventions. The authors first discuss the key principles that should guide policymakers, that is, a focus on the market failures that could justify targeted sectoral interventions, as well as the potential government failures that can undermine these interventions. The authors then discuss some commonly employed policy tools, their rationale, and the associated pitfalls. Finally, the authors outline a stylized decision-making framework.